PARTAI BARU DAN ORANG BARU, ANALISIS KIPRAH PARTAI SOLIDARITAS INDONESIA BALI PERSPEKTIF RANDALL DAN SVASAND - Prastama, I Gede Wega; Noak, Piers Andreas; Pramana, Gede Indra (Jurnal Nawala Politika, 2022)
TheIndonesian Solidarity Party, especially in the Province of Bali, succeeded in bringing three of its cardres to DPRD seats inthe 2019 legislative elections so asto make theauthor interested in researching and analyzing how the new political party works from 2015-2020 according to randall and Svasand's perspective level of Regional Leadership Council of Bali Province To understand the problem, the study used descriptive qualitative methods that relied ona combination ofsecondary informationfrom various sourcesandprimary data from observations, as well asin-depth interviews of informants from psi board of Bali province and elected board members from PSI Bali province. After conducting research, researchers obtained the results that the gait of new political parties with new people could not be done briefly, although with new concepts or ways because there are many stages that must be done so that political parties are able to institutionalize.